2010
DOI: 10.1590/s0031-10492010004700001
|View full text |Cite
|
Sign up to set email alerts
|

Morfologia e duração do desenvolvimento pós-embrionário de Chrysomya megacephala (Diptera: Calliphoridae) em condições de laboratório

Abstract: A morfologia e o tempo de desenvolvimento pós-embrionário de Chrysomya megacephala (Fabricius) criada em condições de laboratório e em dieta de carne bovina, foi descrita e comparada ao de outras espécies. Os parâmetros analisados foram à duração dos instares larvais e a morfologia. Para isso as larvas foram fixadas e preservadas em intervalos de tempo de 2 horas, desde a eclosão das larvas até a 50ª hora, a fim de se determinar o tempo de desenvolvimento de cada estágio. O tempo total de desenvolvimento larva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 26 publications
0
9
1
1
Order By: Relevance
“…A discrepancy with the present description concerns the anterior spinose band on segment a5, which is described by both Florez & Wolff (2009) and Barros‐Cordeiro & Pujol‐Luz (2010) as broadly interrupted. Barros‐Cordeiro & Pujol‐Luz (2010) describe larval spines as very variable in form, with mono‐, bi‐ or tricuspid tips. This is not consistent with our observations, in which all spines were noted as having a monocuspid form (e.g.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…A discrepancy with the present description concerns the anterior spinose band on segment a5, which is described by both Florez & Wolff (2009) and Barros‐Cordeiro & Pujol‐Luz (2010) as broadly interrupted. Barros‐Cordeiro & Pujol‐Luz (2010) describe larval spines as very variable in form, with mono‐, bi‐ or tricuspid tips. This is not consistent with our observations, in which all spines were noted as having a monocuspid form (e.g.…”
Section: Discussioncontrasting
confidence: 99%
“…2C) provided a light microscope photograph of those variable spines, but the caption for the figure does not specify which instar is documented. Further enquiry has confirmed that the illustrated spines belonged to a second‐instar larva and that the first‐instar larvae analysed by Barros‐Cordeiro and Pujol‐Luz (2010) had only monocuspid spines (J. R. Pujol‐Luz, personal communication, 2012). Other publications provide descriptions and figures of only the cephaloskeleton and very general aspects of larval morphology.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations